Boosting Intersubjectivity by Digital Video Recording Project in EFL Classes - Bilal Qureshi; John Roseberry; Zeeshan Qureshi (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2020)
One challenge that modern English teachers face is the how effectively design an interface that monitors output, notices weaknesses, and provides accurate feedback. The ephemeral nature of speech obstructs assessment, peer review, and self-reflection of L2 spoken output for both students and teachers. This study sought to determine if the use of video recording would help solve this problem. Using video camera in phone proved to be a great tool that offers direct benefits to learners. These benefits included providing a tangible record of what was said, a great opportunity for peers to watch the video again for detailed online feedback, and an opportunity for students to reflect on how their oral skills for improvement. This study collected data for one academic semester (16 weeks) from undergraduate students at two universities; 48 South Korean university students and 37 Pakistani university students. The data was analyzed using a mixed method approach. The data was collected in the form of participants’ speech recordings, feedback comments to their peers, self-reflection, and responses from interviews. A meticulous comparison was also provided between all of the university students’ attitudes and performances in speech classes using video recording as a pedagogical tool for peer-feedback, self-reflection, and assessment. Additionally, a comprehensive description was also provided that revealed the students’ perceptions towards recording as a tool to enhance speech skills, the effects of video-recorded in-class speeches, reflection tasks, and online peer feedback. The results concluded that learners had their speaking production skills advanced from using video-recorded speeches. This conclusion was bolstered by already existing research supporting the effectiveness and wide applicability of video-recorded speeches in content-based instruction. More importantly, the study offers some practical tools and policies for setting up a video-recording routine for speech classes. The goal of this study was to engage practitioners about collaborative learning, so they could subsequently implement this information in their own respective classrooms.